Stress factors experienced by nursing and midwifery students - Mrosková, Slávka; Schlosserová, Alena; Cuperová, Jana; Tkáčová, Ľubomíra (Central European Journal of Nursing and Midwifery, 2024)
Aim: Stress negatively affects studentsʼ health, self-esteem, and clinical performance. Although stress has been analyzed on a long-term basis and many clinical stressors are known, some of the factors potentially triggering stress have not been adequately studied, and the results are not consistent. Our research focused on an assessment of the stress intensity that nursing and midwifery students experience and the impact of ward type, difficulty in providing nursing care, and previous experience on perceptions of stress. Design: Cross-sectional study. Methods: The study sample (n = 258) consisted of 65.5% nursing and 34.5% midwifery students who had completed their clinical training in basal pediatric (36.5%), surgical (27.5%), and medical (36.0%) wards. We analyzed stress intensity (0-10), perception of the difficulty in providing nursing care from the studentʼs perspective (0-10), and their previous experience. Results: Across the entire group of students, the stress intensity was 3.84 (SD = 2.71). Students providing care in pediatric wards (M = 4.72) experienced the highest stress intensity, especially when compared to students in medical wards (M = 2.69), (p < 0.001). The provision of care is most demanding in pediatric wards (M = 4.91) compared to surgical (M = 2.97) and medical wards (M = 3.08), (p < 0.001). Difficulty in providing care is significantly associated with stress intensity (r = 0.548). Previous clinical experience reduces the perception of stress. However, we found a significant decrease only in surgical and medical wards. Conclusion: To reduce the perception of stress in pediatric wards, attention needs to be paid to the quality of pre-clinical training focused on pediatric patient care. At the same time, it is important to increase the effectiveness of clinical education in pediatric wards.
Keywords: pracovní stres; Humans; poskytování zdravotní péče; Delivery of Health Care; průzkumy a dotazníky; studenti ošetřovatelství; lidé; Cross-Sectional Studies; Students, Nursing; Occupational Stress; Hospital Departments; Stress, Psychological; Young Adult; průřezové studie; mladý dospělý; nemocniční oddělení; psychický stres; Surveys and Questionnaires